Determinants of Employment and GDP Resilience in the Context of an Economic Crisis: Evidence from EU countries and regions - Svoboda, Ondřej; Applová, Petra (My University, 2016)
There are many studies that analysed impacts of a set of indicators on economic resilience of countries and regions but studies focusing on the differences between the effects of determinants of employment resilience and GDP resilience are missing. This paper is a preliminary attempt to fill that gap by providing a new cross-country as well as cross-regional evidence on the different effect of determinants of resilience measured by GDP and employment. The analytical part of this paper is based on the analysis of employment and GDP resilience of EU countries as well as with the regional NUTS 2 level in the context of the economic crisis from 2008. The main method used in this study is the correlation analysis. Results show the existence of specific determinants for a different type of resilience on the country level (e.g. indicators of economic structure). Determinants connected with human capital show a strong positive relationship concerning both types of resilience on the country as well as the regional level (especially in terms of growth of employment and product).
Determinanty odolnosti zaměstnanosti a HDP odolnosti v kontextu ekonomické krize: důkaz ze zemí a regionů EU
Keywords: resilience; product; employment; recession; economic crisis; odolnost; produkt; zaměstnanost; recese; hospodářské krize